A Revision of Zaeucoila Ashmead (Hymenoptera, Figitidae), Parasitoids of Agromyzidae (Diptera): New Species, Identity, Distribution, and Hosts - Buffington, Matthew L. (2017)
The eucoiline genus Zaeucoila Ashmead is revised. Following a reevaluation combining previously published phylogenetic data and new specimens, Agrostocynips Díaz is synonymized with Zaeucoila. All species included in Zaeucoila are systematically treated, and now amounts to twelve, seven of which are described as new here: Zaeucoila bitiburculata new species, Z. fidalgoii new species, Z. infuscata new species, Z. johnsonii new species, Z. lignys new species, Z. normae new species, Z. patera new species. The following new combinations are proposed and species redescribed: Zaeucoila grenadensis (Ashmead), new combination; Z. robusta (Ashmead), new combination; Z. flavipes (Ashmead), new combination. Agrostocynips diastrophi (Ashmead), Agrostocynips clavatus Díaz, and Agrostocynips enneatoma (Díaz) are new synonyms of Zaeucoila robusta. Zaeucoila incompleta (Kieffer), Z. triangulifera Kieffer, and Z. unicarinata Ashmead are redescribed. Zaeucoila is an unusual genus of Zaeucoilini in its wide distribution area: it can be found from southern Argentina well into the eastern United States and southern Canada; no other zaeucoiline genus shows such a pattern. Host records and geographic data for Zaeucoila are brought up to date, as well as a key to species. Zeucoila are primary parasitoids of Agromyzidae, including Liriomyza trifolii and other species that are notable economic pests of agriculture. Tropideucoila fulvonotata (Kieffer) is transferred to Marthiella (new combination).